Factors affecting the quality of dementia care at acute care hospitals: A cross‐sectional study. Issue 15 (6th September 2021) - Urashima, Shoko; Greiner, Chieko; Ryuno, Hirochika; Yamaguchi, Yuko
Abstract: Aim and Objectives: The purpose of this study was to investigate which factors are associated with the quality of dementia care in acute care hospitals. Background: The number of people with dementia who are admitted to acute care hospitals is increasing. Improving the quality of dementia care in acute care hospitals is an important issue. Prior studies have demonstrated that not only knowledge and nursing experience, but also psychological factors and the nursing practice environment are related to high‐quality care on general wards. Design: Cross‐sectional hypothesis‐testing design. Methods: Participants were nurses providing care to people with dementia at acute care hospitals. Questionnaires were distributed to 300 acute care hospitals in Japan, 10 copies each and 773 valid responses were received. Based on the hypothesis model, variables were tested using multiple regression analysis. The model described the relationship between quality of care, personal attributes and the nursing practice environment. The Strengthening the Reporting of Observational Studies in Epidemiology checklist was used. Results: Almost 90% of the study sample was female, the mean age was 37.4 ± 9.3 years, and the mean nursing experience was 14.0 ± 8.7 years. The results showed that nursing foundations for quality of care, staffing and resource adequacy, specialist consultation, promoting systematic recreation and exchange, knowledge, and feelings towards people with dementia were associated with the quality of dementia care in acute care hospitals. The adjusted coefficient of determination was 0.367. Conclusion: This study identified factors associated with the quality of dementia care in acute care hospitals. Knowledge and feelings towards people with dementia are important, and the nursing practice environment plays an important role in improving the quality of dementia care. Relevance to Clinical Practice: Not only improving nurse's practical ability but also a supportive nursing practice environment enhances the quality of dementia care in acute care hospitals.